Neural Mechanisms of Inflammation-Induced Fever. (August 2018) - Blomqvist, Anders; Engblom, David
Fever is a common symptom of infectious and inflammatory disease. It is well-established that prostaglandin E2 is the final mediator of fever, which by binding to its EP3 receptor subtype in the preoptic hypothalamus initiates thermogenesis. Here, we review the different hypotheses on how the presence of peripherally released pyrogenic substances can be signaled to the brain to elicit fever. We conclude that there is unequivocal evidence for a humoral signaling pathway by which proinflammatory cytokines, through their binding to receptors on brain endothelial cells, evoke fever by eliciting prostaglandin E2 synthesis in these cells. The evidence for a role for other signaling routes for fever, such as signaling via circumventricular organs and peripheral nerves, as well as transfer into the brain of peripherally synthesized prostaglandin E2 are yet far from conclusive. We also review the efferent limb of the pyrogenic pathways. We conclude that it is well established that prostaglandin E2 binding in the preoptic hypothalamus produces fever by disinhibition of presympathetic neurons in the brain stem, but there is yet little understanding of the mechanisms by which factors such as nutritional status and ambient temperature shape the response to the peripheral immune challenge.